Fallacia decussata, sp. nov. : a new marine benthic diatom (Bacillariophyceae) from Northeast Asia - Li, Yuhang; Suzuki, Hidekazu; Nagumo, Tamotsu; Tanaka, Jiro; Sun, Zhongmin; Xu, Kuidong (Phytotaxa, 2015)
Fallacia decussata is described as a new marine littoral diatom from Northeast Asia. Its morphology was examined with light, scanning and transmission electron microscopy. Fallacia decussata has a unique feature, viz., possessing 2–4 pores on each side of raphe terminal fissures, while all congeners have either invariably a single pore or only a slit. This species differs from congeners also by a combination of morphological features including: i) elliptical valves with broadly round poles; and ii) convex and centrally strongly constricted lateral sterna, forming a more or less X-shaped central area; iii) striation density of 25–28 in 10 μm. This species is an epipsammic diatom currently known from intertidal zone in the northwest Pacific Ocean.